Perkembangan peradaban islam pada masa keemasan (golden age): kontribusi terhadap ilmu pengetahuan dan peradaban dunia - Marella, Putri Maya Stephanie (Maliki Interdisciplinary Journal, 2026)
The Islamic Golden Age, which spanned approximately from the eighth to the thirteenth century,represents one of the most influntial periods in the history of word civilization. During this era, Islamic civilization experienced significant advancement in various fields, including science, education, medicine, mathematics, astronomy, philosophy, and culture. This progress was closely related to a strong intellectual spirit rooted in Islamic teachings that emphasize the pursuit of knowledge, rational thinking, and openness to diverse scholarly traditions. The establishment of major centers of learning, such as the House of Wisdom (Bayt al-Hikmah) in Baghdad, played a crucial role in fostering intellectual activies through researsch, scholarly debates, and the translation of scientific works from Greek, Persian, and Indian civilizations. Moreover, prominent Muslim scholars such as Al-Khwarizmi, Ibnu Sina, and Al-Biruni made substansial contributions that not only enriched Islamic scholarship but also influenced the development of Islamic civilizations during the Golden Age by analycing the factors that supported its advancement and the major achievements produced during this period. In addition, this article discusses the impact of Islamic civilization on word civilization and highlights the relevance of its intellectual values in addressing contemporary challenges.